Science and Technology for the Export Product of Small and Medium Sized Enterprise (UKM) Kotaraja Rattan - Muzakir, Ully (Jurnal Ilmiah Peuradeun, 2019)
The objective of the Export Product Science and Technology Division (IBPE) is to boost the export growth of Small and Medium Sized Enterprises (SME) of rattan handicraft products in Aceh Besar Regency "Kotaraja Rotan" through improved management and product quality. The program also aims to accelerate the transfer of technology and management from STKIP Bina Bangsa Getsempena Banda Aceh as the implementer of IBP to SME "Kotaraja Rotan" as an industrial society as well as developing link and match between STKIP Bina Bangsa Getsempena Banda Aceh, SME, Aceh Besar District Government and large community. The method implemented is to provide assistance to the quality of raw materials, production processes, product quality, production management and marketing, quality of manpower, facilities and finance of SME. The conclusion of the program in this first year is the solution offered has successfully solved the problems faced by partners that are marked with the issuance of business license for partners, the availability of mall tools to guarantee the quality of products concerning the size and shape, availability of production space and good and clean showroom with partner needs. This IbPE program has encouraged the public spirit to be able to produce export products in order to compete in the international market.